Advancing and refining archaeological dental calculus research using multiomic frameworks. Issue 1 (1st January 2021) - Wright, Sterling L.; Dobney, Keith; Weyrich, Laura S.
ABSTRACT: Dental calculus (calcified dental plaque) is a cross-cultural biological matrix that is emerging as a critical source of information for anthropologists and oral health professionals. It contains a multitude of diverse biomolecules, providing information about an individual's culture, diet, ancestry, and health. Most researchers who study archaeological dental calculus use genomic or proteomic approaches, although a wide range of other techniques are now available. However, few studies have utilized efficient multiomic protocols. This lack of integration is problematic, as such approaches in other fields have proven to improve results and strengthen interpretations. Our review discusses three multiomic approaches: (1) interactions between the metaproteome and metagenome; (2) relationships between the host genome and oral metagenome; and, (3) associations between the epigenome and metagenome. We draw from multiomic studies on soil, plant, gut, and modern oral microbiomes to demonstrate how such integration can provide insights that are not attainable with single-omic approaches.